A Glu@Zn-Ni MOF material-immobilized glycosyltransferase and its preparation method and application
By modifying Zn-Ni MOF ligand exchange, Glu@Zn-Ni MOF material was prepared, which solved the problem of insufficient enzyme loading and stability, and achieved significant improvement in enzyme loading and long-term maintenance of enzyme activity.
Patent Information
- Application Number
- CN202411035786.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-30
AI Technical Summary
In the prior art, the enzyme loading and stability of the immobilized glycosyltransferase of Zn-Ni MOF material fail to meet expectations and needs to be further improved.
The surface modification of Zn-Ni MOF was prepared by ligand exchange method, and the Glu@Zn-Ni MOF material with nanoflower spheres with outer layer was prepared, further improving the enzyme loading and stability.
The enzyme load was significantly improved, with an increase of 32.67%, and higher enzyme activity was maintained over a wider pH and temperature range. The enzyme activity remained at 83.42% after 7 cycles.
Smart Images

Figure CN118931892B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of immobilized enzyme biocatalysts, and in particular to a glycosyltransferase immobilized on a Glu@Zn-Ni MOF material, and a preparation method and application thereof. Background Art
[0002] Ginsenosides are triterpenoid saponins and the main active ingredients of ginseng. They have anti-aging, antioxidant and anti-cancer properties. Due to the diverse structures produced by the interaction of their unique triterpenoid skeleton with different sugar groups, ginsenosides exhibit multiple biological activities.
[0003] Ginsenoside Rh2, also known as 3-O-β-D-glucopyranosyl-protopanaxadiol, is an expensive and rare PPD-type ginsenoside. Ginsenoside Rh2 has anti-proliferation, anti-invasion, anti-metastasis, cell cycle arrest and differentiation-promoting effects in cancer treatment, but the content of ginsenoside Rh2 in ginseng extract is extremely low (total dry weight 0.0001% to 0.0003% [w / w]). Therefore, the synthesis of ginsenoside Rh2 has received extensive attention.
[0004] The preparation methods of ginsenoside Rh2 include plant extraction, chemical synthesis and synthetic biology cell factory construction. However, these methods are not environmentally friendly, have low yields and cannot be industrialized. In contrast, the enzyme-catalyzed conversion method is green and efficient, and is a promising method for achieving industrial production of ginsenoside Rh2.
[0005] Protopanaxadiol (PPD) is converted to glucose or other sugars in C 3 or C 20 The biosynthetic enzyme uridine diphosphate (UDP)-glycosyltransferase (UGT) used in the glycosylation process can synthesize a variety of ginsenosides by forming O-β1,2- or O-β1,6-glycosidic bonds.
[0006] UGTs are common enzymes in nature and are widely used in the synthesis of oligosaccharides, polysaccharides, glycoconjugates and new derivatives. They are key enzymes in the last step of the biosynthesis of ginsenoside Rh2.
[0007] Metal-organic frameworks (MOFs) are widely used due to their high specific surface area, adjustable and ultra-high porosity, designable functions and good thermal stability. However, in order to make the metal-organic frameworks have better performance, they need to be modified. The surface modification methods of materials include surfactant modification, small molecule modification and polymer modification.
[0008] Among the small molecule modification methods, post-synthetic ligand exchange has been widely used in recent years. This is a simple and mild strategy to modify the original MOFs with various metal ligands. The principle is to introduce new ligands with much smaller pKa values than the original organic ligands. Therefore, carboxylic acid ligands with lower pKa values are more competitive than carboxylic acids with higher pKa values in terms of node connectivity to achieve ligand exchange.
[0009] The study showed that the ligand exchange material has high stability and its ability to immobilize enzymes is significantly improved. The organic ligand contained in the Zn-Ni MOF material in this study is 2-aminoterephthalic acid (pKa = 3.95), while glutamic acid (pKa = 2.13), as a carboxylic acid ligand with a lower price and pKa value than 2-aminoterephthalic acid, is very suitable for use as a new ligand for ligand exchange.
[0010] The invention patent with application number "202311462493.6" "A glycosyltransferase immobilized on a Zn-Ni MOF material and its preparation method and application" synthesizes highly stable mesoporous Zn-Ni MOF nanoparticles by solvothermal method, and then uses mesoporous Zn-Ni MOF nanoparticles to purify and immobilize glycosyltransferase UGT in one step. The immobilized UGT has better pH adaptability, thermal stability, excellent reusability and storage stability; the prepared UGT@Zn-Ni MOF can achieve a higher ginsenoside Rh2 conversion rate when used as an enzyme biocatalyst for catalytic reactions. However, this patent still has the problem that the enzyme loading and stability of the material do not meet expectations, which needs to be further improved. Summary of the invention
[0011] To solve the above problems, the present invention provides a glycosyltransferase immobilized on a Glu@Zn-Ni MOF material and a preparation method and application thereof. The surface of Zn-Ni MOF is modified by a ligand exchange method to prepare a Glu@Zn-Ni MOF material with an outer layer of nanoflower balls, thereby further improving the enzyme loading capacity and stability of the Zn-Ni MOF material.
[0012] To achieve the above object, the present invention provides a method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, comprising the following steps:
[0013] S1. Dispersing Zn-Ni MOF and glutamic acid in a mixed solution of DMF and ethylene glycol for ligand exchange. The ligand exchange process is carried out at room temperature and under magnetic stirring. After the ligand exchange is completed, the precipitate is filtered to obtain a precipitate, and the precipitate is washed and dried to obtain Glu@Zn-Ni MOF powder.
[0014] S2. The Glu@Zn-Ni MOF powder obtained in step S1 is mixed with the cell lysate containing glycosyltransferase in a phosphate buffer solution at pH=7.4, and the mixture is stirred in an ice water bath. After the stirring is completed, the mixture is centrifuged, and the precipitate obtained by centrifugation is the glycosyltransferase UGT@Glu@Zn-Ni MOF immobilized on the Glu@Zn-Ni MOF material.
[0015] Preferably, in step S1, the molar ratio of Zn-Ni MOF to glutamic acid is 1:0.3-3.
[0016] Preferably, in step S1, the ligand exchange reaction time is 1 to 5 hours.
[0017] Preferably, in step S1, the rotation speed of the magnetic stirring is 8000 rpm / min.
[0018] Preferably, in step S1, washing is performed with ethanol and deionized water, and drying is performed at 60° C. for 6 hours.
[0019] Preferably, in step S2, the mass volume ratio of Glu@Zn-Ni MOF powder to cell lysate containing glycosyltransferase is 10 mg: 0.25-1.25 mL.
[0020] Preferably, in step S2, stirring the mixed solution in an ice-water bath comprises: magnetically stirring the mixed solution in an ice-water bath at -4°C for 1.5 hours.
[0021] Preferably, the preparation process of glycosyltransferase UGT comprises: constructing glycosyltransferase expression engineering bacteria BL21-GE02773-28a using glycosyltransferase gene GE02773 mined from the genome of Bacillus subtilis SL-44 and inducing it to express as soluble protein UGT.
[0022] A Glu@Zn-Ni MOF material-immobilized glycosyltransferase prepared by the above-mentioned method for preparing the Glu@Zn-Ni MOF material-immobilized glycosyltransferase.
[0023] An application of a glycosyltransferase immobilized on a Glu@Zn-Ni MOF material as described above in the synthesis of ginsenoside Rh2, wherein uridine diphosphate glucose, protopanaxadiol and glycosyltransferase immobilized on a Glu@Zn-NiMOF material are mixed in a phosphate buffer at a mass ratio of 3:1.2:10 in a pH=7.4, and the mixture is oscillated in a water bath at 40°C for 2 hours, and then extracted with n-butanol to obtain ginsenoside Rh2.
[0024] The present invention provides a Glu@Zn-Ni MOF material-immobilized glycosyltransferase and a preparation method and application thereof, which have the following beneficial effects:
[0025] (1) The present invention provides a method for preparing a glycosyltransferase immobilized on a Glu@Zn-Ni MOF material, wherein the Zn-Ni MOF material is post-synthetically modified by a ligand exchange method, and Glu@Zn-Ni MOF particles with a surface full of nanoflower balls are synthesized, and then Glu@Zn-Ni MOF nanoparticles are used to immobilize a glycosyltransferase (UGT); the specific surface area of Glu@Zn-Ni MOF is 54.53 m 2 / g, while the specific surface area of Zn-Ni MOF material is 21.44m 2 / g, the former is 2.54 times that of the latter, which greatly improves the enzyme loading capacity of the material; when the mass ratio of Zn-Ni MOF and glutamic acid is 1:1, the enzyme loading of Glu@Zn-Ni MOF is 137.61 mg / g, which is 32.67% higher than that of Zn-Ni MOF (103.72 mg / g);
[0026] (2) The enzyme stability experiment shows that UGT@Glu@Zn-Ni MOF exhibits better enzyme activity than free UGT in a wider range of pH and temperature, and the activity of the immobilized enzyme remains at about 83.42% of the initial enzyme activity after 7 cycles of use; when the UGT@Glu@Zn-Ni MOF prepared by the present invention is used as an enzyme biocatalyst for catalytic reaction, a higher conversion rate of ginsenoside Rh2 can be achieved, so it has great industrial application potential in nanotechnology and biocatalysis;
[0027] (3) When the UGT@Glu@Zn-Ni MOF prepared by the present invention is used as an enzyme biocatalyst to synthesize ginsenoside Rh2, the conversion rate is 81.09%, which is higher than the conversion rate of UGT@Zn-Ni MOF as an enzyme biocatalyst to synthesize ginsenoside Rh2.
[0028] (4) The UGT@Glu@Zn-Ni MOF preparation method provided by the present invention has simple and easy-to-obtain raw materials and low cost; the required equipment is relatively conventional and easy to prepare and control.
[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of the Glu@Zn-Ni MOF prepared in Example 2;
[0031] Figure 2 The CLSM test results of UGT@Glu@Zn-Ni MOF prepared in Example 2;
[0032] Figure 3 This is the particle size distribution diagram of Glu@Zn-Ni MOF prepared in Example 2;
[0033] Figure 4 X-ray diffraction patterns of Glu@Zn-Ni MOF of Example 2 and Examples 7 to 10;
[0034] Figure 5 The enzyme loading and enzyme activity test results of Glu@Zn-Ni MOF prepared at different ligand exchange times in Examples 2 and 7 to 10;
[0035] Figure 6 The infrared test result diagram of the Zn-Ni MOF of Example 1 and the Glu@Zn-Ni MOF synthesized by adding glutamic acid and Zn-NiMOF in different proportions in Examples 2 to 6;
[0036] Figure 7 The enzyme loading and enzyme activity test results of Glu@Zn-Ni MOF synthesized by adding different ratios of glutamate and Zn-Ni MOF in Examples 2 to 6;
[0037] Figure 8 The effects of different enzyme addition amounts on the performance of the immobilized enzyme in Examples 2 and 11 to 15 are shown;
[0038] Fig. 9 The effects of different immobilization times on the enzyme loading and enzyme activity of Glu@Zn-Ni MOF in Examples 2 and 16 to 19;
[0039] Fig.10 The relative activity diagram of the UGT@Zn-Ni MOF in Comparative Example 1 and the UGT@Glu@Zn-Ni MOF in Example 2 in the application of synthesizing ginsenoside Rh2 after being recycled for 1 to 7 times;
[0040] Fig.11 The water contact angle measurement diagram of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF in Example 2;
[0041] Fig.12 The N of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF prepared in Example 2 2 Adsorption-desorption curves;
[0042] Fig.13 The pore size distribution curves of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF of Example 2 are shown;
[0043] Fig.14The XPS analysis diagram of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF of Example 2;
[0044] Fig.15 Figure (a) is a fitting curve diagram of the protein secondary structure of UGT@Glu@Zn-Ni MOF in Example 2; Figure (b) is a diagram showing the protein secondary structure ratio of free UGT, UGT@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages disclosed in the embodiments of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the embodiments of the present invention and are not intended to limit the embodiments of the present invention. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0046] Embodiment 1
[0047] A method for preparing a Zn-Ni MOF material, comprising:
[0048] 0.2789 g of zinc nitrate and 0.0906 g of nickel nitrate were dissolved in a mixture of 16 mL of DMF and 10 mL of ethylene glycol, and the mixture was magnetically stirred for 1 h. 0.91 g of 2-aminoterephthalic acid was added and magnetically stirred for 0.5 h to obtain a mixture. The mixture was transferred to a 50 mL polytetrafluoroethylene reactor and kept warm at 150° C. for 8 h to obtain a precipitate. The precipitate was repeatedly washed with ethanol and deionized water, and dried in a vacuum drying oven at 60° C. for 8 hours to obtain a yellow-brown Zn-Ni MOF powder.
[0049] Embodiment 2
[0050] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material comprises the following steps:
[0051] S1. Add 0.10 g Zn-Ni MOF prepared in Example 1 and 0.10 g glutamic acid to a mixed solution of 15 mL DMF and 10 mL ethylene glycol, and stir magnetically for 2 h at room temperature. Centrifuge at 8000 rpm / min and dry at 60° C. for 6 h to obtain Glu@Zn-Ni MOF material.
[0052] S2. Mix 10 mg of the Glu@Zn-Ni MOF powder prepared in step S1 with 1.0 mL of cell lysate containing glycosyltransferase in 10 mL (pH = 7.4) phosphate buffer, stir magnetically in an ice water bath at -4°C for 1.5 h, and centrifuge to obtain Glu@Zn-Ni MOF material-immobilized glycosyltransferase (UGT@Glu@Zn-Ni MOF).
[0053] The preparation of glycosyltransferase includes: using the glycosyltransferase gene GE02773 (the gene sequence has been made public) mined from the genome of Bacillus subtilis SL-44 to construct a glycosyltransferase expression engineering bacterium BL21-GE02773-28a, and finally inducing it to express as a soluble protein UGT. Specifically:
[0054] (1) Add 200 μL of kanamycin and 4 mL of glycosyltransferase expression engineered bacterial culture to 200 mL of liquid culture medium, shake and culture in a 37°C incubator until OD595nm=0.6-0.8, then add 200 μL of IPTG to induce expression, and shake and culture in a 16°C incubator for 12-16 h.
[0055] (2) Extraction process of crude enzyme solution containing glycosyltransferase: The induced bacterial solution was centrifuged at 8000 rpm for 3 min at 4°C, washed twice with PBS buffer at pH = 7.4, and then 20 mL of PBS buffer was added, and the cells were disrupted using a cell disruptor.
[0056] The working parameters of the cell disruptor are: working time 5s, interval time 5s, total working time 20min. Finally, the crude enzyme solution was obtained by centrifugation at 12000rpm for 10min at 4°C.
[0057] The configuration of phosphate buffer with pH=7.4: Phosphate buffer contains 137mmol / L NaCl, 2.7mmol / L KCl, 10mmol / L Na 2 HPO 4 , 2mmol / LKH 2 PO 4 Weigh 7.946 g of NaCl, 0.201 g of KCl, 3.581 g of Na 2 HPO 4 , 0.272 g of KH 2 PO 4 Prepare 1000 mL of solution and adjust pH to 7.4.
[0058] Embodiment 3
[0059] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that: in step S1, the Zn-Ni MOF powder is 0.15 g, and the mass of glutamic acid is 0.05 g.
[0060] Embodiment 4
[0061] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that in step S1, the mass of Zn-Ni MOF powder is 0.1334 g, and the mass of glutamic acid is 0.0667 g.
[0062] Embodiment 5
[0063] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that in step S1, the mass of Zn-Ni MOF powder is 0.0667 g, and the mass of glutamic acid is 0.1334 g.
[0064] Embodiment 6
[0065] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that in step S1, the mass of Zn-Ni MOF powder is 0.05 g, and the mass of glutamic acid is 0.15 g.
[0066] Embodiment 7
[0067] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that: in step S1, the magnetic stirring time is 1 hour.
[0068] Embodiment 8
[0069] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that: in step S1, the magnetic stirring time is 3 h.
[0070] Embodiment 9
[0071] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that: in step S1, the magnetic stirring time is 4 hours.
[0072] Embodiment 10
[0073] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that: in step S1, the magnetic stirring time is 5 h.
[0074] Embodiment 11
[0075] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that in step S2, the volume of the cell lysate containing the glycosyltransferase is 0.25 mL.
[0076] Embodiment 12
[0077] A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that in step S2, the volume of the cell lysate containing the glycosyltransferase is 0.5 mL.
[0078] Embodiment 13
[0079] A method for preparing glycosyltransferase immobilized on a Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that in step S2, the volume of the cell lysate containing the glycosyltransferase is 0.75 mL.
[0080] Embodiment 14
[0081] A method for preparing glycosyltransferase immobilized on a Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that in step S2, the volume of the cell lysate containing the glycosyltransferase is 1.25 mL.
[0082] Embodiment 15
[0083] A method for preparing glycosyltransferase immobilized on a Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that in step S2, the volume of the cell lysate containing the glycosyltransferase is 1.5 mL.
[0084] Embodiment 16
[0085] A method for preparing glycosyltransferase immobilized on a Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that: in step S2, magnetic stirring is performed in an ice-water bath at -4°C for 1 hour.
[0086] Embodiment 17
[0087] A method for preparing glycosyltransferase immobilized on a Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that: in step S2, magnetic stirring is performed in an ice-water bath at -4°C for 2 hours.
[0088] Embodiment 18
[0089] A method for preparing glycosyltransferase immobilized on a Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that: in step S2, magnetic stirring is performed in an ice-water bath at -4°C for 2.5 hours.
[0090] Embodiment 19
[0091] A method for preparing glycosyltransferase immobilized on a Glu@Zn-Ni MOF material, wherein the specific steps are the same as those in Example 2, except that: in step S2, magnetic stirring is performed in an ice-water bath at -4°C for 3 hours.
[0092] Comparative Example 1
[0093] The immobilized glycosyltransferase is prepared using the Zn-Ni MOF material in Example 1, comprising:
[0094] 10 mg of Zn-Ni MOF powder was mixed with 0.25 mL of cell lysate containing glycosyltransferase in a phosphate buffer solution at pH = 7.4, magnetically stirred in an ice water bath at 4°C for 2.5 h, and centrifuged to obtain glycosyltransferase immobilized on Zn-NiMOF material (UGT@Zn-Ni MOF).
[0095] Comparative Example 2
[0096] The free glycosyltransferase was used to catalyze the synthesis of ginsenoside Rh2, and its conversion rate was detected to be 88.24%.
[0097] Free glycosyltransferase was used to synthesize ginsenoside Rh2, specifically: 3 mg of uridine diphosphate glucose, 1.2 mg of protopanaxadiol and 0.25 mL of free glycosyltransferase were mixed in a phosphate buffer at pH = 7.4, shaken in a 40°C water bath for 2 h, and finally extracted with 800 μL of n-butanol to obtain ginsenoside Rh2.
[0098] Since the free glycosyltransferase is in liquid form and is mixed with the phosphate buffer solution (PBS buffer) at pH=7.4, it cannot be recycled after use.
[0099] Experimental Testing
[0100] (a) If Figure 1As shown, this is a scanning electron microscope image of the Glu@Zn-Ni MOF prepared in Example 2. It can be seen that after ligand exchange, a new layer of nano-flower balls is gradually generated on the surface of the Zn-Ni MOF material to form a new MOF material. Since the surface of the new MOF material is full of nano-flower balls, its specific surface area is increased several times accordingly, and the enzyme loading capacity of the material is also improved accordingly.
[0101] In order to investigate the distribution of the enzyme after it was immobilized on the material, the UGT@Glu@Zn-Ni MOF prepared in Example 2 was subjected to CLSM testing, and the results are shown in the figure. Figure 2 As shown in (a) and (b), (a) is the CLSM image in the fluorescent state, and (b) is the CLSM image in the non-fluorescent state. It can be seen that the surface of the UGT@Glu@Zn-Ni MOF material and the inward extending area emit uniform green fluorescence, which indicates that the glycosyltransferase is evenly distributed on the surface of Glu@Zn-Ni MOF and the enzyme loading is high.
[0102] And we can clearly see that there is an obvious stratification, which may be caused by the nano-flower ball layer formed on the surface of the material. From the CLSM image, we can see that the glycosyltransferase is evenly distributed in the Glu@Zn-Ni MOF and the enzyme loading is high.
[0103] like Figure 3 As shown in the figure, it is the particle size distribution diagram of Glu@Zn-Ni MOF prepared in Example 2. It can be seen from the figure that the particle size distribution of Glu@Zn-Ni MOF is relatively uniform, of which the particle size is 615.14nm accounting for 39.49%, and the particle size is 712.38nm accounting for 43.55%. The particle sizes of the remaining small part are 531.17nm (3.90%) and 824.99nm (13.05%). The test results show that the particle size of Glu@Zn-Ni MOF is basically in the range of 615.14nm-712.38nm.
[0104] (ii) Figure 4 As shown, the X-ray diffraction patterns of Glu@Zn-Ni MOF prepared at different ligand exchange times in Examples 2 and 7 to 10 show that the XRD results of the materials synthesized at different ligand exchange times are basically the same, with only slight differences. Among them, NiO 2 The (003) crystal plane of Zn(OH) is 2θ=20.095°, 2θ=27.114°, 2θ=42.010° and 2θ=52.225°, respectively. 2 (110), (120), (112) and (132) crystal planes.
[0105] like Figure 5As shown, the enzyme loading and enzyme activity test results of Glu@Zn-Ni MOF prepared under different ligand exchange times in Examples 2 and 7 to 10. The results show that the enzyme loading and enzyme activity of Glu@Zn-Ni MOF gradually increase with the increase of ligand exchange time. When the ligand exchange time is 2h, the material can reach the maximum enzyme loading and enzyme activity. At this time, the enzyme loading of Glu@Zn-Ni MOF is 112.87mg / g, and the relative enzyme activity is 99.00%. Therefore, the optimal time for ligand exchange is 2h.
[0106] (III) Figure 6 As shown, the infrared test results of the Zn-Ni MOF of Example 1 and the Glu@Zn-Ni MOF synthesized by adding different ratios of glutamic acid and Zn-Ni MOF in Examples 2 to 6 are shown. It can be seen from the figure that when the ratio of glutamic acid to Zn-NiMOF is 3:1, the functional group changes of the material are more obvious.
[0107] like Figure 7 As shown, the enzyme loading and enzyme activity test results of Glu@Zn-Ni MOF synthesized by adding different ratios of glutamate and Zn-Ni MOF in Examples 2 to 6.
[0108] As can be seen from the figure, as the amount of Zn-Ni MOF increases, the enzyme loading and enzyme activity of Glu@Zn-Ni MOF gradually increase. When the dosage ratio of glutamate and Zn-Ni MOF is 1:1, the enzyme loading and relative enzyme activity of Glu@Zn-Ni MOF reach the highest, at which the enzyme loading is 137.61 mg / g and the relative enzyme activity is 88.11%. However, when the dosage of glutamate increases, the enzyme loading and enzyme activity of Glu@Zn-Ni MOF gradually decrease. It can be seen that the optimal dosage ratio of glutamate and Zn-Ni MOF is 1:1
[0109] (IV) Figure 8 As shown, the effects of different enzyme addition amounts on the performance of immobilized enzymes in Examples 2 and 11 to 15 are shown. As can be seen from the figure, with the increase in the amount of enzyme added, the enzyme loading of the material gradually increases. When 1.0 mL of crude enzyme solution is added to every 10 mg of Glu@Zn-Ni MOF material, the material can reach the maximum enzyme loading and enzyme activity. At this time, the enzyme loading is 113.10 mg / g, and the relative enzyme activity is 87.63%. Compared with the optimal enzyme addition amount of unmodified Zn-Ni MOF of 0.25 mL crude enzyme solution / 10 mg material, the optimal enzyme addition amount of Glu@Zn-Ni MOF has increased by 3 times.
[0110] (V) Fig. 9As shown, the effect of different immobilization times on the enzyme loading and enzyme activity of Glu@Zn-NiMOF in Example 2 and Examples 16 to 19. As can be seen from the figure, as the immobilization time increases, the enzyme loading of the material gradually increases. When the immobilization time is 2h, the enzyme loading is the highest, which is 89.09mg / g. However, the relative enzyme activity of the immobilized enzyme is only 71.19% at this time. As the immobilization time continues to extend, the enzyme loading and relative enzyme activity of the material gradually decrease. When the immobilization time is 1.5h, the enzyme loading of the material is 83.24mg / g, and the relative enzyme activity is 86.84% at this time.
[0111] (VI) Ginsenoside Rh2 was synthesized using the UGT@Zn-Ni MOF in Comparative Example 1 and the UGT@Glu@Zn-Ni MOF in Example 2, specifically:
[0112] 3 mg of UDP-glucose was mixed with 1.2 mg of protopanaxadiol and 10 mg of UGT@Zn-Ni MOF or UGT@Glu@Zn-Ni MOF in a phosphate buffer at pH 7.4, shaken in a 40°C water bath for 2 h, and finally extracted with 800 μL of n-butanol to obtain ginsenoside Rh2.
[0113] Ginsenoside Rh2 was synthesized using UGT@Zn-Ni MOF in Comparative Example 1, with a conversion rate of 78.74%.
[0114] Ginsenoside Rh2 was synthesized using the UGT@Glu@Zn-Ni MOF in Example 2 with a conversion rate of 81.09%.
[0115] like Fig.10 As shown, (a) is the relative activity diagram of 1 to 7 cycles of UGT@Glu@Zn-Ni MOF in Example 2 for synthesizing ginsenoside Rh2, and (b) is the relative activity diagram of 1 to 7 cycles of UGT@Zn-Ni MOF in Comparative Example 1 for synthesizing ginsenoside Rh2. It can be seen that UGT@Glu@Zn-Ni MOF still retains 83.42% of the initial enzyme activity after 7 cycles. Compared with the recyclability of UGT@Zn-Ni MOF (75.99%), the stability of the modified Glu@Zn-Ni MOF material has been significantly enhanced.
[0116] (VII) Fig.11 As shown, the Glu@Zn-Ni MOF ( Fig.11 (a)) and UGT@Glu@Zn-NiMOF( Fig.11 Water contact angle measurement diagram in (b).
[0117] As can be seen from the figure, the water contact angle of Glu@Zn-Ni MOF is 19.3°, while the water contact angle of the existing Zn-Ni MOF is 18.8°, indicating that the material has become more hydrophobic after ligand exchange. Moreover, the water contact angle of UGT@Glu@Zn-Ni MOF is 36.55°, and the water contact angle of the material has increased significantly after the enzyme has been immobilized, indicating that the introduction of the enzyme has greatly increased the hydrophobicity of the material, making it easier to separate it from the catalytic reaction system for reuse.
[0118] (VIII) Fig.12 As shown, the N of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF prepared in Example 2 2 Adsorption-desorption curve. It can be seen that the N 2 The adsorption-desorption curves all show type IV adsorption isotherms, which is consistent with the isotherm type of typical mesoporous materials.
[0119] (IX) Fig.13 As shown, it is a pore size distribution curve diagram of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF of Example 2. It can be seen that the pore size of Glu@Zn-Ni MOF is 3.72nm, while the pore size of UGT@Glu@Zn-Ni MOF after loading the enzyme is 4.55nm.
[0120] As shown in Table 1, the specific surface area, pore volume and pore capacity of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF prepared in Example 2 are shown.
[0121] Table 1
[0122]
[0123] The specific surface area of Glu@Zn-Ni MOF is 54.53 m 2 / g, while the specific surface area of Zn-Ni MOF is 21.44m 2 / g, the specific surface area of the material increased by 1.54 times after ligand exchange modification. In addition, the pore volume of the material increased from 0.055cm 3 / g becomes 0.12cm 3 / g, and the pore size changed from 3.72nm to 4.55nm. After the enzyme was immobilized on Glu@Zn-Ni MOF, both the pore volume and pore size increased. This may be because the introduction of the enzyme changed the surface environment of the material, causing its pore volume and pore size to increase. In fact, the increase in pore volume and pore size is more conducive to the contact between substrate and enzyme, improving the efficiency of catalytic reaction.
[0124] (10) Fig.14 Shown are XPS analysis diagrams of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF according to Example 2 of the present invention.
[0125] Fig.14 (a) is a full spectrum analysis, from which it can be seen that the elements that make up Glu@Zn-Ni MOF are mainly C, N, O, Zn, and Ni, while the full spectrum of UGT@Glu@Zn-Ni MOF also identifies the S element, indicating that UGT@Glu@Zn-Ni MOF contains protein, indicating that UGT is successfully immobilized on Glu@Zn-Ni MOF.
[0126] Fig.14 Figure (b) shows the peak fitting results of N1s and N2 of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF. Compared with Glu@Zn-Ni MOF, the N1s peak of UGT@Glu@Zn-Ni MOF is significantly enhanced, indicating the successful immobilization of the enzyme. The peaks of 401.15 eV and 400.81 eV in the N1s spectrum indicate the presence of C-NH 2 .
[0127] Fig.14 Figure (c) shows the peak fitting results of Zn2p of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF. 1 / 2 and Zn2p 3 / 2 The peaks at 1021.88eV and 1044.91eV in the spectrum ( Fig.10 The middle ((c) figure) are the characteristic peaks of ZnO.
[0128] Fig.14 Figure (d) shows the peak fitting results of Ni2p of Glu@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF. The peaks at 856.00eV and 855.89eV in the Ni2p spectrum are Ni 2 O 3 and characteristic peaks of NiO.
[0129] After enzyme immobilization, the peaks of Zn, Ni and N in Glu@Zn-Ni MOF all moved to lower binding energies, which may be due to the change in the surface chemical environment of the material caused by the addition of enzymes. In addition, after the Glu@Zn-Ni MOF material was loaded with UGT, the peak intensity of each element decreased significantly, while the peak intensity of XPS was proportional to the concentration of the surface element and the atomic sensitivity factor. In addition, the imidazole group on UGT and the Zn on Glu@ZnNi MOF 2+ and Ni 2+After chelation, Ni 2 O 3 Or when the ZnO content decreases, the peak value also moves.
[0130] (XI) Fig.15 As shown, part (a) is the protein secondary structure fitting curve diagram of UGT@Glu@Zn-Ni MOF in Example 2; part (b) is the protein secondary structure ratio diagram of free UGT, UGT@Zn-Ni MOF and UGT@Glu@Zn-Ni MOF.
[0131] After UGT was fixed on Glu@Zn-Ni MOF, the proportion of β-turn and β-fold structure decreased significantly, while the proportion of α-helix structure and random coil structure increased significantly. This shows that UGT has a flexible conformation after being immobilized by Glu@Zn-Ni MOF, which is conducive to stabilizing the transition state through conformational adjustment during the catalytic process. However, compared with UGT@Zn-Ni MOF, the proportion of β-fold structure of UGT@Glu@Zn-Ni MOF is higher. β-fold together with α-helix in protein constitutes the basic skeleton of the overall conformation. The increase in the proportion of β-fold indicates that the rigidity of the modified Glu@Zn-Ni MOF immobilized enzyme has increased, which may be the reason for the higher stability of the modified material.
[0132] In summary, the preparation method of the Glu@Zn-Ni MOF material immobilized glycosyltransferase provided by the present invention synthesizes highly stable Glu@Zn-Ni MOF nanoparticles by solvothermal method, and then uses mesoporous Glu@Zn-Ni MOF nanoparticles to immobilize glycosyltransferase (UGT) in one step, and the immobilized UGT has better pH adaptability, thermal stability, excellent reusability and storage stability. The Glu@Zn-Ni MOF prepared by the present invention has strong specific adsorption performance for UGT with histidine tag, and when the UGT@Glu@Zn-Ni MOF prepared by the present invention is used as an enzyme biocatalyst for catalytic reaction, a higher ginsenoside Rh2 conversion rate can be achieved, which has great industrial application potential in nanotechnology and biocatalysis.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing glycosyltransferase immobilized on Glu@Zn-Ni MOF material, characterized in that: The steps include: S1. Dispersing Zn-Ni MOF and glutamic acid in a mixed solution of DMF and ethylene glycol for ligand exchange. The ligand exchange process is carried out at room temperature and under magnetic stirring. After the ligand exchange is completed, the precipitate is filtered to obtain a precipitate, and the precipitate is washed and dried to obtain Glu@Zn-Ni MOF powder. S2, mixing the Glu@Zn-Ni MOF powder obtained in step S1 with the cell lysate containing glycosyltransferase in a phosphate buffer solution at pH=7.4, stirring the mixture in an ice water bath, centrifuging the mixture after stirring, and the precipitate obtained by centrifugation is the glycosyltransferase UGT@Glu@Zn-Ni MOF immobilized on the Glu@Zn-Ni MOF material; In step S1, the preparation method of Zn-Ni MOF includes: dissolving 0.2789g zinc nitrate and 0.0906g nickel nitrate in a mixed solution of 16mL DMF and 10mL ethylene glycol, magnetically stirring for 1h, adding 0.91g 2-aminoterephthalic acid, magnetically stirring for 0.5h to obtain a mixture, transferring the mixture to a 50mL polytetrafluoroethylene reactor, keeping the mixture at 150°C for 8h to obtain a precipitate, repeatedly washing the precipitate with ethanol and deionized water, and drying it in a vacuum drying oven at 60°C for 8h to obtain Zn-Ni MOF powder; In step S1, the molar ratio of Zn-Ni MOF to glutamic acid is 1:0.3-3; In step S1, the ligand exchange reaction time is 1 to 5 hours; In step S2, the mass volume ratio of Glu@Zn-Ni MOF powder to cell lysate containing glycosyltransferase is 10 mg: 0.25-1.25 mL; In step S2, stirring the mixed solution in an ice-water bath comprises: magnetically stirring the mixed solution in an ice-water bath at -4°C for 1.5 hours.
2. The method for preparing a glycosyltransferase immobilized on a Glu@Zn-Ni MOF material according to claim 1, characterized in that: In step S1, the rotation speed of the magnetic stirring is 8000 rpm / min.
3. The method for preparing a glycosyltransferase immobilized on a Glu@Zn-Ni MOF material according to claim 1, characterized in that: In step S1, washing is performed with ethanol and deionized water, and drying is performed at 60° C. for 6 hours.
4. The method for preparing a glycosyltransferase immobilized on a Glu@Zn-Ni MOF material according to claim 1, characterized in that: The preparation process of glycosyltransferase UGT includes: using the glycosyltransferase gene GE02773 mined from the genome of Bacillus subtilis SL-44 to construct a glycosyltransferase expression engineering bacterium BL21-GE02773-28a and inducing it to express as a soluble protein UGT.
5. A Glu@Zn-Ni MOF material-immobilized glycosyltransferase prepared by the method for preparing a Glu@Zn-Ni MOF material-immobilized glycosyltransferase as described in any one of claims 1 to 4.
6. Use of the glycosyltransferase immobilized on the Glu@Zn-Ni MOF material as claimed in claim 5 in the synthesis of ginsenoside Rh2, characterized in that: The application is as follows: uridine diphosphate glucose, protopanaxadiol and glycosyltransferase immobilized on Glu@Zn-Ni MOF material are mixed in a phosphate buffer at pH=7.4 according to a mass ratio of 3:1.2:10, the mixed solution is oscillated in a water bath at 40°C for 2 hours, and then extracted with n-butanol to obtain ginsenoside Rh2.
Citation Information
Patent Citations
A Zn-Ni MOF material-immobilized glycosyltransferase and its preparation method and application
CN117511899B
Biocompatible metal-organic framework material glutamic acid-zinc and preparation and application thereof
CN106987580A
Zn-NiMOF material immobilized glycosyl transferase as well as preparation method and application thereof
CN117511899A